Shedding Light on Living Cells. (2nd December 2014) - Antognazza, Maria Rosa; Martino, Nicola; Ghezzi, Diego; Feyen, Paul; Colombo, Elisabetta; Endeman, Duco; Benfenati, Fabio; Lanzani, Guglielmo
Abstract : An overview of the optical methods available to modulate the cellular activity in cell cultures and biological tissues is presented, with a focus on the use of exogenous functional materials that absorb electromagnetic radiation and transduce it into a secondary stimulus for cell excitation, with high temporal and spatial resolution. Both organic and inorganic materials are critically evaluated, for in vitro and in vivo applications. Finally, as a direct practical application of optical‐stimulation techniques, the most recent results in the realization of artificial visual implants are discussed. Abstract : Optical stimulation of cells and tissues is becoming a key technology in biology and medicine due to the high spatial and temporal resolutions achievable. Recent advances in materials science are providing new ways to transduce light excitation into biochemical stimuli, expanding the available tools for the understanding of complex interactions in biological systems.